Virus-like particles containing the extracellular domain of G protein in combination with a CTL peptide of M2 elicit protection against respiratory syncytial virus infection without pulmonary disease - Qin, Huan; Luo, Jin; Pan, Zishu (Frontiers in Immunology, 2025)
Background and aimsRespiratory syncytial virus (RSV) is a major respiratory pathogen afflicting both infants and the elderly. Although three RSV vaccines have been approved for adults over the age of 60 or pregnant individuals, there are ongoing efforts to develop novel vaccines against RSV infection. This study was designed to develop and evaluate virus-like particles (VLPs) as potential RSV subunit vaccine candidates, with the goal of balancing immunogenicity, protective efficacy, and safety.MethodsTwo types of VLPs were constructed using a recombinant baculovirus (rBV)-insect cell expression system: GECD-VLPs (containing the extracellular domain [GECD] of RSV G protein) and GECD/M282-90-VLPs (containing GECD fused with the CTL epitope M282-90 of M2 protein). BALB/c mice were vaccinated with these VLPs, and immune responses were assessed via RSV-specific IgG and neutralizing antibody titers, cytokine profiles (IFN-γ, IL-2, TNF-α, IL-10, IL-4, IL-5), and lung T-cell subsets (CD25+FoxP3+ Treg and Th17 cells). Protective efficacy against RSV infection and immunopathology was further evaluated post-challenge.ResultsVaccination with both VLPs induced robust RSV-specific IgG and neutralizing antibodies, conferring defense against RSV infection. Compared with the UV-RSV control group, both GECD/M282-90-VLPs and GECD-VLPs groups exhibited significantly increased Th1-type cytokine levels and decreased Th2-type cytokine concentrations (P<0.05, P<0.001). Importantly, compared to GECD-VLPs, GECD/M282-90-VLPs further significantly upregulated the expression of Th1-type cytokines (IFN-γ, IL-2) and regulatory cytokine IL-10, while significantly downregulating Th2-type cytokine IL-4 (all P<0.05). Post-RSV challenge, mice vaccinated with GECD/M282-90-VLPs exhibited a substantially increased proportion of CD25+FoxP3+ Treg cells and a decreased percentage of Th17 cells in the lungs. Notably, GECD/M282-90-VLP vaccination prevented RSV-induced immunopathology.DiscussionOur findings demonstrate that vaccination with GECD/M282-90-VLPs elicited a balanced immune response and conferred protection against RSV infection without immunopathology. These data demonstrate that the GECD/M282-90-VLPs are a potential RSV subunit vaccine candidate.